2018
DOI: 10.1002/jnr.24259
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal hormones modulate the HPA‐axis and the SNS in response to psychosocial stress

Abstract: Exposure to stress activates both the hypothalamus-pituitary-adrenal (HPA) axis and the sympathetic nervous system (SNS). A growing body of research points to the contribution of sex hormones (testosterone, estrogen, and progesterone), the end products of the hypothalamus-pituitary-gonadal (HPG) axis, in modulating stress reactivity. The present study aimed at investigating the potential modulating role of sex hormones on HPA and SNS reactivity to psychosocial stress. The reactivity, induced by the Trier Socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 72 publications
(106 reference statements)
0
18
0
Order By: Relevance
“…A formal assessment in those with postoperative basal cortisol between 80 and 325 nmol/L or symptoms suggestive of AI is advised at least 6 weeks after surgery. Reliability of testing can be optimized when testing is postponed in case of concomitant factors that can potentially affect ACTH and cortisol secretion and/or its bioavailability, i.e diabetes insipidus, SIADH, CSF-leakage, fever, and oral contraceptive use in the 6 weeks before testing [26].…”
Section: Discussionmentioning
confidence: 99%
“…A formal assessment in those with postoperative basal cortisol between 80 and 325 nmol/L or symptoms suggestive of AI is advised at least 6 weeks after surgery. Reliability of testing can be optimized when testing is postponed in case of concomitant factors that can potentially affect ACTH and cortisol secretion and/or its bioavailability, i.e diabetes insipidus, SIADH, CSF-leakage, fever, and oral contraceptive use in the 6 weeks before testing [26].…”
Section: Discussionmentioning
confidence: 99%
“…Although sex hormones may influence intrusive memories, the inconsistent finding highlight the need for future research to further delineate the relationship between specific hormones and intrusive memories. Given that both intrusive memories and estradiol are associated with limbic network activation [52, 53], and that estradiol modulates noradrenergic activity which is associated with intrusive memories [15, 54, 55], it is important to examine the potential interaction of sex and stress hormones on intrusive memories following trauma exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Pandemic restriction and isolation by quarantine during COVID-19 are acting as sources of stress [ 120 ]. Cumulating evidence suggest that gender based response to stress probably results from differential modulation of HPA axis by sex hormones [ 121 ]. Both clinical as well as experimental models reported that exposure to stress in initial life enhance the risk of development of psychosocial disorders in males [ 122 ].…”
Section: Probable Factors Responsible For Higher Mortality Rate Amongmentioning
confidence: 99%